THE RELATIONSHIP BETWEEN UNDERGRADUATE GPA AND UKMPPD CBT SCORE OF MEDICAL STUDENTS AT UDAYANA UNIVERSITY IN MAY 2022 - Vedanti, I Gusti Ayu Ika Frangipani; Ganesha, I Gde Haryo; Mayura, I Putu Bayu; Sundariyati, I Gusti Ayu Harry (E-Jurnal Medika Udayana, 2025)
The Competency Test for Medical Professional Program Students (UKMPPD) is a test to standardize the quality of Indonesian doctors. However, the number of students who fail on Computer-Based Test (CBT) UKMPPD were increasing, as well as at Udayana University. Undergraduate Grade Point Average (GPA) considered related to the UKMPPD pass rates. Several studies related to those relationship have been conducted, but showed varied results. This research aims to determine the relationship between undergraduate GPA and UKMPPD CBT score among students of Faculty of Medicine, Udayana University, May 2022. This study is a cross-sectional analytical study using secondary data obtained from Academic Division of Faculty of Medicine, Udayana University, with a total of 181 students as  participants. The data were analyzed using SPSS ver. 25 with univariate, bivariate, and multivariate analyses. The study were dominated by females (64.1%), 23 years old (42.5%), and students of batch 2016 (97.8%). There was a significant positive moderate relationship between undergraduate GPA and UKMPPD CBT score (p = 0.000; r = 0.564). The results of the multivariate analysis showed that undergraduate GPA was a variable that significantly and consistently associated with UKMPPD CBT score (coefficient = 24.052; correlation coefficient = 0.601; p = 0.000 (< 0.001)). This study showed that there was a significant positive moderate relationship between undergraduate GPA and UKMPPD CBT score. This variable was significantly and consistently related to the UKMPPD CBT score compared to three variables tested simultaneously. Keywords: undergraduate GPA, UKMPPD CBT score, medical students